The use of non-bronchoscopic brushings to study the paediatric airway - Lane, C.; Burgess, S.; Kicic, Anthony; Knight, D.A.; Stick, S. (BMC, 2005)
Background: The use of cytology brushes for the purpose of obtaining respiratory cells from adults for clinical and research purposes is well established. However, the safety and utility of non-bronchoscopic brushings to study the paediatric airway has not been assessed. The purpose of this study was to assess the practicality of using non-bronchoscopic brushing to sample epithelial cells from children for investigation of epithelial function in health and disease using a wide range of molecular and cellular techniques. Methods: Non-bronchoscopic brushing was investigated in a non-selected cohort of healthy, and mildly asthmatic children presenting for surgery unrelated to respiratory conditions, at the major children's hospital in Perth. Safety and side-effects of the procedure were assessed. Cell number, phenotype and viability were measured for all samples. The potential of these cells for use in long-term cell culture, immunohistochemistry, western blotting, quantitative PCR and gene arraying was examined. Results: Non-bronchoscopic brushing was well tolerated in all children. The only significant side effect following the procedure was cough: nursing staff reported cough in 20% of patients; parents reported cough in 40% of patients. Cells sampled were of sufficient quantity and quality to allow cell culture in 93% of samples. Similarly, protein and RNA extracted from the cells was suitable for investigation of both gene and protein expression using micro-array and real-time PCR. Conclusions: Non-bronchoscopic brushing in children is safe and easy to perform, and is not associated with any complications. Using this technique, adequate numbers of epithelial cells can be retrieved to allow cell culture, western blotting, real time PCR, and microarray analysis. The purpose of this study is to demonstrate the utility of non-bronchoscopic airway brushing to obtain and study epithelial cells and to encourage others so that we can accelerate our knowledge regarding the role of the epithelium in childhood respiratory disease. © 2005 Lane et al., licensee BioMed Central Ltd.